Land Waqf Practices Based on Local Wisdom of Tribes In Dosay Village, Papua - Muhammad Abdulloh; Athi’ Hidayati; Moh Nurul Qomar; Abdurrohman Kasdi (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
Papua, which is a part of Indonesia, has a vibrant ethnic culture. Traditions are frequently tied to religion in practice. Waqf is an Islamic principle that does not necessarily contradict regional traditions. The purpose of this study is to describe the land waqf practices in the Papuan community of Dosay. With its subject in Papua’s Dosay village, this study used a descriptivequalitative methodology. The conclusion of this study is that there is an additional mechanism for implementing waqf, namely one based on Customary law, particularly through approval from Ondoafi as the head of tradition, who has rights to all land and all of its natural resources in a customary territory, or through customary deliberations.In Dosay village, the land waqf was given support for the implementation of Islamic worship, and Ondoafi fully backed this up by demonstrating that he had been given waqf land for free to use for religious services, proselytizing, education, and public facilities. However, the administration of waqf certificates, which have not fully utilized all existing assets, continues to be a problem. Despite Islam being a minority faith, the consequences of this study offer examples of religious moderation in waqf practice.